Role of heparin in microvascular free flap surgery in head and neck reconstruction - Agrawal, Gunjan; Gupta, Ashutosh; Choudhary, Vivek; Tiwari, Santanu; Verma, Kshitij; Dubey, Hitesh (International Surgery Journal, 2016)
Background:Microsurgical reconstructions for free flap transfer have been highly successful applications in the past decades. Antithrombotic prophylactic agents, such as low molecular- weight heparin, aspirin and dextran have been routinely used for the prevention of microvascular thrombosis. Even though these agents are efficacious in microsurgery, some systemic morbidity is still reported. Methods: The present prospective study was conducted in the Department of Surgical Oncology, Regional cancer center, Pt. JNMC, Raipur (C.G.), India from the January 2014 to June 2015. Each patient was informed and consent was taken to participate in the study. Detailed clinical history and examination of the patients was recorded. All Investigations relevant to the study were done before the surgical procedure. Outcome of the surgery were noted. Data was compiled in MS Excel and checked for its completeness and correctness. Then it was analyzed. Results:During the study period, 20 microsurgery operations on 20 patients were performed. There were 17 male and 3 female patients. In all patients neck dissection was done and resective part was reconstructed with free flap. Out of 20 free flap 12 radial artery free flaps and 8 free fibula flap was harvested. Conclusions:The free flap technique is safe but involves a significant learning period and requires careful postoperative monitoring of the patient. Early intervention is important for the salvage of free flaps and for lowering the failure rate.